The cyclic oxidation behavior of a Pt modified γ' nanocrystalline coating at 1150 ℃. (November 2022) - Xiao, Qin; Huang, Qinying; Yang, Lanlan; Ren, Pan; Yang, Yingfei; Wang, Qiwei; Li, Wei; Zhu, Shenglong; Wang, Fuhui
Abstract: A Pt modified γ' nanocrystalline coating (Pt-NC γ' coating) was manufactured and its cyclic oxidation behavior was examined and compared to that of Pt-diffused γ/γ' and β-NiPtAl coatings at 1150 ℃. The Pt-NC γ' coating showed its advantages in suppressing the precipitation of topologically closed-packed phases and resisting to rumpling behavior. The nanocrystalline structure promoted the Pt-NC γ' coating to develop an exclusive α-Al2 O3 scale with low Pt and Al content, which exhibited superior spalling resistance than oxide scale formed on Pt-diffused γ/γ' coating. The mechanisms for the superior oxide-spalling resistance and rumpling resistance of the Pt-NC γ' are discussed. Highlights: A Pt modified γ' nanocrystalline coating was manufactured and investigated. The Pt-NC γ' coating mitigates interdiffusion and suppresses the precipitation of TCP phases. The nanocrystalline structure reduces the required Al and Pt content to form exclusively Al2 O3 . The Pt-NC γ' coating exhibits high rumpling resistance.